2010
DOI: 10.1111/j.1749-7345.2009.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Glycerol from Biodiesel Production as a Feed Ingredient for Channel Catfish,Ictalurus punctatus

Abstract: Glycerol is the main by‐product of biodiesel production from vegetable oils and animal fats. It has been evaluated as an energy source for several farm animals. A study was conducted to examine the effects of various levels of glycerol in channel catfish, Ictalurus punctatus, diets. Fish with mean initial weight of 6.8 ± 0.1 g were stocked in 110‐L flow‐through aquaria and fed practical diets containing 0, 5, 10, 15, and 20% glycerol for 9 wk. There were no significant differences in feed consumption, weight g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
52
2
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 11 publications
11
52
2
6
Order By: Relevance
“…In fish liver, malic enzyme is little affected by changes on the nature of dietary carbohydrates (Dias et al, 2004). In the present study, no significant differences were observed between treatments in the hepatic activity of the malic enzyme, considering that some authors consider glycerol as a carbohydrate source (Li et al, 2010). The obtained results suggest that fish fed 10 and 15% glycerol in their diet used glycerol as the lipogenic substratum in liver and muscle, given the higher activity of the G6PD hepatic enzyme and the higher amount of triglycerides found in these tissues.…”
Section: Resultsmentioning
confidence: 35%
See 3 more Smart Citations
“…In fish liver, malic enzyme is little affected by changes on the nature of dietary carbohydrates (Dias et al, 2004). In the present study, no significant differences were observed between treatments in the hepatic activity of the malic enzyme, considering that some authors consider glycerol as a carbohydrate source (Li et al, 2010). The obtained results suggest that fish fed 10 and 15% glycerol in their diet used glycerol as the lipogenic substratum in liver and muscle, given the higher activity of the G6PD hepatic enzyme and the higher amount of triglycerides found in these tissues.…”
Section: Resultsmentioning
confidence: 35%
“…The obtained results suggest that Nile tilapia juveniles have the ability to use glycerol as a substrate for tissue lipogenesis, indicating a greater fat deposition in the liver and muscle of fish, a not-desired feature due to the lack of consumer acceptance of fillet fat. However, Li et al (2010) found significantly lower liver lipid concentrations in channel catfish fed 15 and 20% glycerol than in those fed lower glycerol levels. This inconsistency may be related to the different feeding habits of the studied species.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Estudos envolvendo a utilização do glicerol bruto na dieta de peixes iniciaram-se com o bagre-docanal, porém, sem levar em conta o valor digestível desse ingrediente (LI et al, 2010). Posteriormente foi relatado seu potencial uso como fonte energética para tilápia-do-nilo (MEURER et al, 2012), pacu e jundiá (BALEN et al, 2014).…”
Section: Introductionunclassified